2024
DOI: 10.1021/acsnano.3c07002
|View full text |Cite
|
Sign up to set email alerts
|

Precise Photodynamic Therapy by Midkine Nanobody-Engineered Nanoparticles Remodels the Microenvironment of Pancreatic Ductal Adenocarcinoma and Potentiates the Immunotherapy

Chengming Qu,
Haitao Yuan,
Ming Tian
et al.

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is notorious for its resistance against chemotherapy and immunotherapy due to its dense desmoplastic and immunosuppressive tumor microenvironment (TME). Traditional photodynamic therapy (PDT) was also less effective for PDAC owing to poor selectivity, insufficient penetration, and accumulation of photosensitizers in tumor sites. Here, we designed a light-responsive novel nanoplatform targeting the TME of PDAC through tumor-specific midkine nanobodies (Nbs), which could e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Tumor tissues often exhibit high heterogeneity, characterized by an elevated ROS and glutathione (GSH) content in tumor cells. GSH, a primary cellular reducing agent, counteracts the therapeutic effects of PDT by clearing excessive ROS. Ferroptosis, a form of cell death relying on ROS-induced lipid peroxidation (LPO), has emerged as a promising strategy in tumor therapy. Unlike other forms of cell death, ferroptosis involves oxidative damage to polyunsaturated fatty acids, disrupting cell structure and integrity. Glutathione peroxidase 4 (GPX4), a key regulator of ferroptosis and a downstream product of GSH, plays a crucial role in mitigating LPO toxicity by catalyzing the reduction of hydrogen peroxide (H 2 O 2 ) and LPO to nontoxic lipid alcohol (LOH).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor tissues often exhibit high heterogeneity, characterized by an elevated ROS and glutathione (GSH) content in tumor cells. GSH, a primary cellular reducing agent, counteracts the therapeutic effects of PDT by clearing excessive ROS. Ferroptosis, a form of cell death relying on ROS-induced lipid peroxidation (LPO), has emerged as a promising strategy in tumor therapy. Unlike other forms of cell death, ferroptosis involves oxidative damage to polyunsaturated fatty acids, disrupting cell structure and integrity. Glutathione peroxidase 4 (GPX4), a key regulator of ferroptosis and a downstream product of GSH, plays a crucial role in mitigating LPO toxicity by catalyzing the reduction of hydrogen peroxide (H 2 O 2 ) and LPO to nontoxic lipid alcohol (LOH).…”
Section: Introductionmentioning
confidence: 99%
“…PDT, akin to PTT, employs photosensitizers to generate cytotoxic reactive oxygen species (ROS) upon light exposure, damaging tumor cells by disrupting cell membranes and intracellular biomacromolecules. In addition, it has been reported that ROS can inhibit the activity of HSP, amplifying the effectiveness of PTT. Compared to complex nanoplatforms loaded with both photothermal agents and photosensitizers, phototheranostic agents capable of generating both ROS and local heating offer simplicity and safety advantages in synergizing PTT and PDT. , Moreover, synergistic PTT and PDT induce stronger immunogenic cell death (ICD) response, which is characterized by the release of damage-associated molecular patterns (DAMPs) such as calreticulin (CRT) exposure, extracellular release of adenosine triphosphate (ATP), and high mobility group box B1 (HMGB1), and release tumor-associated antigens, activating the immune system and facilitating tumor eradication. …”
mentioning
confidence: 99%